Detecting emotions through non-invasive wearables - Rincon, J. A. (2018)
Current research on computational intelligence is being conducted in order to emulate and/or detect emotional states using specific devices such as wristbands or similar wearables. In this sense, this paper proposes the use of intelligent wristbands for the automatic detection of emotional states in order to develop an application which allows us to extract, analyse, represent and manage the social emotion of a group of entities. Nowadays, most of the existing approaches are centred in the emotion detection and management of a single entity. The designed system has been developed as a multi-agent system where each agent controls a wearable device and is in charge of detecting individual emotions based on bio-signals.